Innovation in Early Chilhood Education in the Global Era: Integration of Cultural Understanding, Psychological Insight, and Literatur Skills - Nidya Chairunnisa Kusumaayu; Firyal Dewi Noffitria; Aulia Putri Andrianti; Masyitah Fildzah Luthfiyanti; Rahma Ajeng Widhanty (Proceeding International Symposium on Global Educatiorg Psychology, and Cultural Synergy, 2025)
Globalization demands innovation in early childhood education (PAUD) that focuses not only on cognitive aspects but also on the integration of cultural values, psychological insights, and literacy skills. This literature review aims to identify forms of early childhood education innovation that are relevant to the needs of the 21st century and encompass a multidisciplinary approach in their development. The results of the review indicate that PAUD education innovations include the use of interactive technology, local culture-based learning, socio-emotional approaches, and strengthening early literacy. The implications of this study emphasize the importance of collaboration between educators, psychologists, and cultural communities in building a sustainable and inclusive early childhood education framework.